Skill composition and regional entrepreneurship: a comparative study between Germany and Portugal - Joana Mendonça; Christoph Grimpe (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
The question whether agglomeration externalities arise either from specialization or diversification of economic activity has since long been a major topic in the analysis of factors determining economic growth. In this paper we analyze whether a more specialized or a more diverse skill composition of labor in regions affects the level of new firm entries in general as well as in technology- and knowledge-intensive subsectors. We compare Germany and Portugal which exhibit, though EU member states, different institutional infrastructures for entrepreneurship. Based on a harmonized dataset, our results indicate that the skill composition has different effects on firm entry in the two countries. More specifically, for Portugal the specialization of skills has a positive effect on the level on new firm entry in all sectors. In contrast to this, our results for Germany reveal exactly the opposite effect. These results suggest that both specialization and diversity theories hold, and that the effect thus may depend on other more local and regional factors.
Keywords: J24; L26; O57; R11; 330; Entrepreneurship; skill composition; regional analysis; comparative study; Unternehmensgründung; Region; Qualifikation; Berufsstruktur; Arbeitsteilung; Diversifikation; Vergleich; Deutschland; Portugal